2019
DOI: 10.1186/s12909-019-1833-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with successful dementia education for practitioners in primary care: an in-depth case study

Abstract: BackgroundWith increasing numbers of people in the UK living with dementia, the provision of good quality person-centred care that meets the often complex needs of this population is required. Given the majority of people with dementia live in the community, significant care and support will be provided by primary care services. This means the primary care workforce needs appropriate education to ensure they have the right knowledge, skills and attitudes to meet these care needs. However, little is understood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The second theme drive from findings was the use of supplements.Research has proven that high doses of individual vitamins, including vitamin B, vitamin D, selenium, other vitamins, and calcium, does not clearly benefit for improving cognition in people who are well-nourished. Coconut oil is being used in the prevention or treatment of Alzheimer"s disease is a topic of immense interest for the researchers; however, no significant research is conducted in this regard up till now (Surr, 2019).…”
Section: Discussion:-mentioning
confidence: 99%
“…The second theme drive from findings was the use of supplements.Research has proven that high doses of individual vitamins, including vitamin B, vitamin D, selenium, other vitamins, and calcium, does not clearly benefit for improving cognition in people who are well-nourished. Coconut oil is being used in the prevention or treatment of Alzheimer"s disease is a topic of immense interest for the researchers; however, no significant research is conducted in this regard up till now (Surr, 2019).…”
Section: Discussion:-mentioning
confidence: 99%
“…Our review showed that some studies are specifically dealing with GP/FM education or training to improve person-centered care (22)(23)(24). However, in most of the studies retained, personcentered care as a learning objective is usually mentioned together with other topics such as shared decision making, comprehensive approach, empowerment, compassionate care, etc.…”
Section: Person-centered Carementioning
confidence: 99%
“…(25)(26)(27)(28)(29)(30)(31). Moreover, person-centered care and these other topics are often seen as indirect objectives to be taught when organizing training programs around themes as dementia, multimorbidity, or clinical care of refugees (22)(23)(24). Gillies pleas for medical humanity as an academic discipline and resource for education (32).…”
Section: Person-centered Carementioning
confidence: 99%
“…The research took place in a range of health and social care provider organisations in the UK, who were delivering dementia care. These included acute hospitals, Mental Health Trusts, social care services (care homes), and [16][17][18][19] and an overview is presented below.…”
Section: Settingmentioning
confidence: 99%
“…study aimed to investigate the components of effective dementia training and education, and the barriers and facilitators to its implementation. This was achieved through a systematic literature review [3], a national audit of 386 dementia training programmes in the UK [16], a survey of staff who had completed dementia training and ten organisational mixed-methods case studies in acute hospitals (n = 3) [17], mental health Trusts (n = 3), care homes (n = 3) [18], and primary care (n = 1) [19].…”
Section: Introductionmentioning
confidence: 99%